(untitled) (Communications in Computational Chemistry, 2022)
In the present paper, the non-radiative transition S_1→S_0 of pyrazine was investigated by employing the improved Born-Oppenheimer adiabatic approximation, in which the conical intersection is shown to be avoided. Vibrational frequencies, normal coordinates, and non-adiabatic coupling matrix elements were obtained by ab initio quantum chemical methods. Calculated rate constants of internal conversion S_1→S_0 are τ(υ=0)=61.7 ps and τ(υ=1)=61.2 ps in good agreement with the experimental findings.